Sistem Informasi Inventory Barang Berbasis Website Pada PT. Oasis Water International Bogor - Siti Faizah; Eni Pudjiarti (Elkom: Jurnal Elektronika dan Komputer, 2026)
PT. Oasis Water International is a company engaged in bottled drinking water (AMDK). This research aims to design and build an information system that can efficiently manage inventory at PT. Oasis Water International, which operates in the bottled water production sector. Currently, inventory management in the company is still conducted manually, using unintegrated recording methods, resulting in inefficiencies, recording errors, and delays in data processing. The method used in this research is the First-In First-Out (FIFO) method to ensure that the first items in are the first items out, thereby minimizing the risk of losses due to expired products. This research also employs the Rapid Application Development (RAD) approach in software development to accelerate the design and implementation process of the system. The results of this research are expected to improve operational efficiency, reduce storage costs, and enhance customer satisfaction by providing accurate and real-time information regarding inventory. With the implementation of this web-based information system, PT. Oasis Water International is expected to address existing issues and improve performance and competitiveness in the bottled drinking water industry.